Study of the molecular mechanisms involved in cell differentiation of embryonic stem cells - Leyva, Ivette Pacheco (2014)
Potential heart progenitors from postnatal and adult heart have been identified in rodents and humans, and were shown to differentiate in vitro into mature cardiomyocytes. However, in some studies only immature cardiac cells were obtained, leading to concerns about whether the inefficient cell electrical maturation and electrical coupling of derivative cells will cause arrhythmias upon cellular therapies of injured hearts. Notwithstanding these concerns, recent clinical assays have indicated an improvement of heart function and life quality of patients treated with autologous cardiac progenitor cells. With the discovery of the capacity of embryonic stem cells (ESC) to differentiate into all lineages, including the cardiovascular lineage, many researchers have been focusing on developing strategies to efficiently direct ESC differentiation for the production of unlimited numbers of cardiomyocytes. Yet, the low efficiency of cardiac differentiation, its teratogenic nature and the lack of reliable protocols to purify the desired cells from ESC cultures are holding back their use for clinical application. Hence, understanding the molecular mechanisms that regulate commitment and differentiation of diverse muscle and non-‐muscle cell lineages of the heart is essential to improve current therapies and to design novel heart stem cell-‐ based therapeutic strategies for cardiac regenerative medicine. Many transcription factors, including Nkx2.5, Gata4 and Isl1, have been described as master regulators of cardiac morphogenesis. Indeed, they are required for the commitment and differentiation of cardiac progenitors in early embryonic development, as well as for the differentiation of ESC into cardiovascular lineages. Furthermore, mutations in these genes have been associated with congenital heart defects in humans. This finding underscores the clinical relevance of studying the role of cardiac transcription factors during heart development. Cited2 is a transcriptional regulator essential for mouse embryonic development. Amongst a wide spectrum of developmental defects presented by Cited2 knockout mouse embryos, the cardiovascular and left-‐right patterning defects are the most prominent. Importantly, heterozygous mutations of human CITED2 in association with congenital heart disease have been reported by several research groups. Moreover, it has been suggested that Cited2 is important for ESC-‐derived cardiovascular development and essential in the epiblast or its derivatives for normal cardiac left-‐right patterning. Although Cited2 was shown to be required for the maintenance of pluripotency and self-‐renewal of ESC, its role in early embryonic development and its mechanism of action are still not well explored. In the present study, we investigated the role of Cited2 in mouse ESC differentiation towards cardiac cells. By performing increasing and absence of Cited2 expression in ESC, we have established that Cited2 is essential for cell commitment and differentiation towards the mesoderm, ectoderm and endoderm lineages. Indeed, Cited2 depletion impaired ESC differentiation to several cell lineages. More importantly, Cited2 was required for the normal emergence of mesoderm cells from early ESC specification to cardiac lineages. Our results suggest that this response is primarily associated with the direct or indirect modulation of Nodal and Brachyury gene expression during mesodermal cell commitment, thus enabling a signaling cascade promoting cardiogenesis. Additionally, our results indicated that loss of Cited2 generated comparatively less cardiomyocytes in differentiated ESC cultures, whereas gain of Cited2 led to higher numbers of cardiomyocytes. These findings suggest Cited2 is an important protein for cardiac function. Furthermore, our data suggest that Cited2 can modulate the gene expression (Islet1, Gata4, Nkx2.5 and Tbx5) in cardiac progenitors, thus playing an important role during cardiac cell commitment. We have also found that Cited2 plays a role in cardiomyocyte proliferation, as indicated by the downregulation of Tbx5 and its targets genes upon Cited2 depletion. Furthermore, by overexpressing human CITED2 and Gata4 in murine ESC, we found that Cited2 could not prevent endoderm commitment induced by Gata4 overexpression. The same overexpression approach was used to test the role of CITED2-‐ISLET1 interaction in cardiac differentiation, and the results indicate that the cardiogenic response of Cited2 might be additive in association with that induced by Islet1 (Isl1) overexpression. We have also found Cited2 expression in multipotent cardiac progenitor population, specifically in secondary heart field (SHF) progenitors, which are marked by the expression of Isl1 protein. Our data generated by increasing and absence of Cited2 Cited2 expression in SHF progenitor, suggest that finely regulated Cited2 gene expression levels could allow or disrupt the SHF-‐differentiation program. Moreover, by performing GST-‐pull down and by bi-‐molecular fluorescence complementation assays, we gathered evidence indicating that CITED2 physically interacts with ISL1. By performing chromatin immunoprecipitation assays we have also found that CITED2 binds the Isl1 promoter region. Taken together, our results indicate that Cited2 is important for proper cardiovascular differentiation by acting at different levels during cardiac stem cell commitment: firstly, by inducing ESC towards mesoderm at early events during ESC commitment; and secondly, by inducing and maintaining the expression of cardiac transcription factors important for cardiogenesis. Although many Cited2 functions remain uncovered, our data indicate that Cited2 is an important cardiac differentiation regulator that can participate in heart regeneration, and therefore be useful for the development of alternative approaches to treat or prevent heart failure,